P387 THE PROGNOSTIC ROLE OF ST2L AND SST2 IN PATIENTS WHO UNDERWENT CAROTID PLAQUE ENDATERECTOMY: A FIVE–YEAR FOLLOW–UP STUDY. (18th May 2022) - Scicchitano, P; Marzullo, A; Cortese, F; Ciccone, A; Angiletta, D; Pulli, R; Massari, F; Caldarola, P; Ciccone, M
Abstract: Background: Soluble suppressor of tumorigenity (sST)–2 plasma concentrations are related to atherosclerosis. The aim of the study was to assess the prognostic impact of sST2 and its membrane–associated form (ST2L) in patients with carotid atherosclerotic plaque who underwent endarterectomy (CEA). Methods: 82 consecutive patients (age range: 48–86 years) who underwent CEA were enrolled. Anthropometric, clinical, instrumental, and laboratory evaluations were gathered. Thirty–seven (45%) patients were symptomatic for cerebrovascular diseases. Patients underwent a five–year follow–up. Phone calls and the analysis of national and regional databases were adopted in order to evaluate the occurrence of the primary outcome (all–cause mortality). The populations was divided according to survival status. Results: Statins were administered in 81% and 87.5% of survivors and non–survivors, respectively. sST2 levels were higher in non–survivors as compared to survivors (117.0 ± 103.9 vs 38.0 ± 30.0ng/mL, p < 0.001) and in symptomatic individuals as compared to asymptomatic (80.3 ± 92.1 ng/mL vs 45.4 ± 41.4 ng/mL, p = 0.02). ROC curve analysis identified sST2 cut–off: > 98.44 ng/mL as the best predictor for mortality. At one year follow–up, survival rate decreased up to 20% in patients with sST2 higher than the cut–off value. At multivariate regression analysis sST2 (HR: 1.012, 95% CI: 1.008–1.016, p < 0.0001) and triglycerides plasma levels (HR: 1.008, 95% CI: 1.002–1.015, p = 0.0135) remained significantly associated to all–cause death. Conclusions: sST2 may act as independent prognostic determinant of all–cause mortality and symptomatic cerebrovascular diseases in patients with carotid atherosclerotic plaque who underwent CEA.